Boron-boron single bonds mimicking transition metals - Himmel, Hans-Jörg (European journal of inorganic chemistry, 2025)
This review article deals with a special transition-metal-like reactivity of ambiphilic (electrophilic and nucleophilic) diborane molecules with a B-B single bond, namely the ability to coordinate a substrate and reduce it in their coordination sphere with the electrons from the B-B bond. Specially designed diboranes are synthesized for this purpose, being Lewis-acidic at boron and at the same time providing a filled B-B bond orbital of high energy, from which electrons could be transferred to the substrate. A fine tuning of the substituents at the boron is required to balance the ambiphilic (electrophilic and nucleophilic) properties of the diborane. Moreover, diborane stability is an important issue for larger-scale applications, since strongly electrophilic diboranes are generally air sensitive. The discussion in the last sections focuses on diboranes with guanidinate substituents. These diboranes are air-stable and easy-to-handle sources of ambiphilic cationic diboranes and are efficiently synthesized by B-B dehydrocoupling reactions. They are particularly suitable for processes in which substrate coordination and electron transfer proceed in two separate steps. The development of a transition-metal-like reactivity with stable, easy-to-handle diboranes paves the way to widen the applications of diboranes for further applications in synthetic chemistry.
Gesehen am 08.12.2025